ANALISIS PEMBELAJARAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM MENINGKATKAN KREATIVITAS ANAK USIA DINI - Abim Shoheri; Nanda Putri Konservasionita Sembiring; Dekristiani Zai; Winda Sherly Utami; Sri Indriani Harianja (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of the Pancasila Student ProfileStrengthening Project (P5) in enhancing the creativity of early childhood learnersat TK Fania Salsabila Barokah. The research employed a qualitative descriptivemethod, with data collected through observations and interviews involving threeteachers. The findings reveal that project-based activities, such as a traditionalcostume fashion show under the theme “I Love Indonesia,” successfullyencouraged children to think creatively, express themselves, and explore newideas. However, the implementation faced several challenges, including limitedtime, a lack of teacher understanding regarding project planning and execution,and inadequate facilities and infrastructure. Project-based learning has proven tobe effective in developing children’s creativity by offering real, interactive, andcontextually relevant learning experiences